2020
DOI: 10.2147/jpr.s257018
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preemptive Nalbuphine Attenuates Remifentanil-Induced Postoperative Hyperalgesia After Laparoscopic Cholecystectomy: A Prospective Randomized Double-Blind Clinical Trial</p>

Abstract: Background: Remifentanil-induced hyperalgesia (RIH) is a paradoxical phenomenon that may increase sensitivity to painful stimuli. Nalbuphine, which is both a μ-receptor antagonist and κ-receptor agonist, may affect RIH. The aim of this study was to evaluate the effects of nalbuphine on RIH during laparoscopic cholecystectomy. Methods: A total of 96 patients were divided into the following four groups: 0.4 μg/kg/min of remifentanil with 0.2 mg/kg of nalbuphine (HRNA), 0.4 μg/kg/min of remifentanil with saline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The inflammation-induced hyperexcitability of extrinsic visceral afferents is associated with nociceptive and opioid receptors [ 27 ], which are related to potentiation of hypersensitivity and hyperalgesia [ 28 ]. The results were unexpected; to the best of our knowledge, there is no report about the effect of nalbuphine on visceral hyperalgesia, although we have reported that nalbuphine can improve remifentanil-induced hyperalgesia (RIH) [ 29 ]. Perhaps the results of the current study can provide some hints for future investigation of nalbuphine in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation-induced hyperexcitability of extrinsic visceral afferents is associated with nociceptive and opioid receptors [ 27 ], which are related to potentiation of hypersensitivity and hyperalgesia [ 28 ]. The results were unexpected; to the best of our knowledge, there is no report about the effect of nalbuphine on visceral hyperalgesia, although we have reported that nalbuphine can improve remifentanil-induced hyperalgesia (RIH) [ 29 ]. Perhaps the results of the current study can provide some hints for future investigation of nalbuphine in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because nalbuphine has very weak reactivity with delta (δ) receptors, this drug is expected to cause reduced irritability or anxiety 5,6 . In the clinical setting, pretreatment with nalbuphine can effectively reduce propofol‐induced injection pain and propofol consumption as well as ameliorate postoperative hyperalgesia induced by high‐dose remifentanil or sufentanil 7–9 . Nalbuphine exhibits a higher therapeutic index owing to its reduced incidence of adverse events (AEs), but has analgesic effects similar to those of morphine 10 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…It reduced the PO visceral pain and supplemental analgesic use 21 and was also useful in ameliorating PO hyperalgesia induced by high-dose remifentanil use in LC. 22 …”
Section: Discussionmentioning
confidence: 99%